Analisis Efektivitas Penggunaan SIPD Dalam Mendukung Transparansi Keuangan Pada Kecamatan Padangsidimpuan Utara Kota Padangsidimpuan Provinsi Sumatera Utara - Namora Lubis , Amiroh Kamilah; Sembiring, Yetty; Dewi Martha, Fitri Yull; Ilham, Rozali (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
This study aims to evaluate the effectiveness of the implementation of the Regional Government Information System (SIPD) in supporting transparency and accountability in financial management at the sub-district level, particularly in Padangsidimpuan Utara Sub-district. Through direct observation during an internship program, this study identifies key aspects of SIPD usage, including system alignment with user needs, interface usability, data input speed, reporting transparency, and the availability of verification and validation features. The evaluation results indicate that while SIPD meets the basic needs of financial reporting and provides an audit trail feature, the system still faces several technical challenges, such as limited data integration, server disruptions, and delays in data input due to suboptimal interdepartmental coordination. Furthermore, the evaluation of the previous year’s Work Plan (Renja) implementation revealed gaps between budget targets and actual realizations, serving as a critical basis for future system and workflow improvements. Therefore, enhanced training, technical support, and better coordination systems are needed to optimize the overall utilization of SIPD.